Squeal suppression approaches of a disc brake assembly - Saw, Chun Lin (2009)
Brake squeal is an annoying noise emanating from a car disc brake and is typically a single-tone, high-pitch noise. In general, brake noise can be divided into three groups: low frequency noise (below 1 kHz), low frequency squeal (1 kHz to 3 kHz), and high frequency squeal (4 to 15 kHz). To date, there are a number of approaches have been proposed and implemented to suppress disc brake squeal but very few are effective to suppress and eliminate it. This thesis proposes an approach to suppress disc brake squeal noise, ranging from 1 to 10 kHz, through structural modification using the finite element method. First, a three dimensional finite element (FE) model of a real disc brake assembly is developed and validated. Then, complex eigenvalue analysis made available in commercial FE software package is performed to determine stability of the brake system where positive real parts of the complex eigenvalue indicate unstable system and in turn exhibit squeal generation in the brake assembly. Then, various structural modifications on the disc, brake pad, caliper and carrier are proposed to reduce the brake squeal. A good modification should be able to reduce and eliminate squeal at various brake operating conditions.